Pengenalan Aplikasi Matematika dalam Kehidupan Sehari-hari pada Anak Panti Asuhan - Susilo Talidobel; M. Chothibul Umam Assa’ady; Baiq Nadia Nirwana; Mohamad Yudisa Putrajip; Wanda Nabila (Rajawali Media Utama, 2023)
This community dedication aims to introduce the application of mathematics to children in orphanages. Through this activity, children are expected to understand that mathematics is not only theoretical, but also has practical applications in everyday life. The dedication methods used involve discussion, demonstration, and interactive use of mathematical applications tailored to children's level of understanding. The evaluation was conducted to measure children's understanding and interest in mathematics after the intervention.